Fluidmistar Media in Inquiry to Improve the Creative Thinking Skills of Senior High School Students - Susilawati Susilawati; Edi Daenuri Anwar (Phenomenon : Jurnal Pendidikan MIPA, 2023)
Learning media an important role in supporting the learning process as a tool for students to gain mastery of the material. This study aims to produce valid fluidmistar media and analyze the increase in students' creative thinking skill after using fluidmistar learning media. Research and development is a method specifically using the ADDIE development model. The data collection technique used was a test of creative thinking skills and a student response questionnaire. The results of the expert's assessment stated that fluidmistar media was feasible to use improve creative thinking skills through inquiry learning. The implementation of fluidmistar media in inquiry learning was applied to students of senior high school in Sragen, Central Java with a total sample of 58 students. Student responses to the Fluidmistar learning media obtained good category. The results of students' positive responses indicate that the developed media to improve students' creative thinking skill and positive responses. The increase in creative thinking skill can be seen based on the pretest and posttest score tested through the N-gain test obtained at 0.74 in the high category. Fluidmistar learning media is suitable for use in inquiry learning to improve students' creative thinking skills on dynamic fluid material.Keywords: fluidmistar media; inquiry; creative thinking skillMedia pembelajaran memberikan peranan penting dalam menunjang proses pembelajaran  sebagai  alat  bantu  bagi  siswa  untuk  mencapai  penguasaan materi. Penelitian ini bertujuan untuk menghasilkan media fluidmistar yang valid dan menganalisis peningkatan kemampuan berpikir kreatif siswa setelah implementasi menggunakan media pembelajaran fluidmistar. Penelitian dan pengembangan    merupakan   metode   yang   khusus   menerapkan   model pengembangan ADDIE. Teknik pengumpulan data yang digunakan adalah tes keterampilan  berpikir kreatif  dan  angket  respon  siswa.  Hasil  penilaian  ahli menyatakan bahwa media fluidmistar layak digunakan untuk meningkatkan kemampuan  berpikir  kreatif  melalui  pembelajaran  inkuiri.  Implementasi media  fluidmistar  dalam  pembelajaran  inkuiri  diterapkan  pada  siswa  salah satu SMA Muhammasiyah 2 Gemolong Jawa Tengah dengan jumlah sampel 58  siswa.  Hasil  validasi  ahli  media  diperoleh  hasil  rekomendasi  dari  aspek data  dan  grafik  (90%),  kombinasi  warna  (92%),  pemilihan  teks  (88%), relevasi  konten  (86%),  presentasi  audio  visual  (85%)  and  efektivitas  media pembelajaran (87%). Media Fluidmistar dinyatakan layak digunakan sebagai media    pembelajaran    konsep    fluida.    Respon    siswa    terhadap    media pembelajaran Fluidmistar diperoleh kategori baik. Hasil respon positif siswa menunjukkan   bahwa   media   yang   dikembangkan   dapat   meningkatkan keterampilan  berpikir  kreatif  siswa  dan  respon  positif.        Peningkatan keterampilan  berpikir  kreatif  dapat  dilihat  berdasarkan  skor  pretest  dan posttest yang diuji melalui uji N-gain diperoleh sebesar0,74 dengan kategori tinggi. Media pembelajaran fluidmistar cocok digunakan dalam pembelajaran inkuiri  untuk  meningkatkan  kemampuan  berpikir  kreatif  siswa  pada  materi fluida dinamis.